Yield rate of chromosomal microarray analysis in fetuses with congenital heart defects. (February 2018) - Turan, Sifa; Asoglu, Mehmet Resit; Benziv, Rinat Gabbay; Doyle, Lauren; Harman, Christopher; Turan, Ozhan M.
Abstract: Objective: The purpose of this study was to calculate the yield rates of CMA in fetuses diagnosed with various CHDs in a tertiary center. Study design: This cohort study collected prenatal genetic test results of 145 fetuses diagnosed with CHD. All 145 cases underwent Conventional karyotype (CK), followed by CMA in cases of negative CK result. "Detection rate" of genetic abnormalities was calculated as the percentage of cases with genetic abnormalities identified. The rate of genetic abnormalities detected by CK was first calculated, and then the cumulative detection rate was calculated in the study population. " Yield rate of CMA" was determined by subtracting the cumulative detection rate from the detection rate of CK. The cumulative detection rate was assumed to represent the detection rate of CMA since it is due to the fact that if CMA had been done for all patients before CK, it would have diagnosed all the genetic abnormalities in the study population, and thus it was named as anticipated CMA. Results: Of the 145 CHD cases, 92 (63.4%) had isolated CHD and 53 (36.6%) had concomitant CHD and extracardiac anomaly (ECA). The detection rate of genetic abnormalities was 14% and 33.8% for CK and anticipated-CMA respectively ( p <  .001). The yield rate of CMA was 19.8% and 16.1% before and after the exclusion of cases with 22q.11.2 deletion/duplication, respectively. The detection rates of genetic abnormalities for isolated CHD, and concomitant CHD-ECA groups were 6.5% and 26.4% by CK, and 23.9% and 50.9% by anticipated-CMA, respectively ( p  < .01). The yield rate of CMA was 17.4% and 24.5% for isolated CHD and concomitant CHD-ECA cases, respectively. Conclusion: CMA increases the diagnostic yield in fetuses with CHD, regardless of whether it is isolated or not. CMA should be the modality of choice when investigating the genetic origin of CHDs until whole exome or genome sequencing is implemented into routine clinical practice.